Effects of Neo-Adjuvant Chemotherapy on CD8 + Serum Levels in Local Advanced Stage Breast Cancer Patients - Nopriansyah Darwin; Nur Qodir; Mulawan Umar; Theodorus (Sriwijaya Journal of Surgery, 2020)
Introduction: CD8 + CTLs are important components of tumor specific cellular adaptive immunity in breast cancer. Chemotherapy can increase the response of cytotoxic lymphocytes and provide anti-tumor immunity. Therefore, chemotherapy can cause cell death and trigger tumor antigens that are processed by APC and activate CD8 + cells to destroy tumor cells. Evaluation of the immune system before treatment can predict chemotherapy response. The purpose of this study was to assess the effect of neo-adjuvant chemotherapy on serum CD8 + levels in patients with locally advanced breast cancer. Methods: Non-comparative clinical trials were conducted at Dr. Mohammad Hoesin Hospital Palembang from October 2017 to June 2018.The sample of this study was 30 breast cancer patients who met the inclusion criteria. All samples underwent FAC neo-adjuvant chemotherapy and data were analyzed with SPSS version 21. Results: The mean age of advanced breast cancer patients was 45.97 Â± 10,526 years with an age range of 30-66 years. Serum CD8 + levels after chemotherapy decreased significantly compared to before chemotherapy (p = 0.000). The value of serum CD8 + before chemotherapy has a sensitivity of 42.86% and specificity of 43.48% with a cut of point of 660.7 cells / mm3. Conclusion: Neo-adjuvant chemotherapy significantly decreases serum CD8 + levels in local advanced breast cancer patients.